2013
DOI: 10.5846/stxb201106300977
|View full text |Cite
|
Sign up to set email alerts
|

Bioindicators and Biomonitors in Environmental Quality Assessment

Abstract: Classical programs for environmental monitoring have been supplemented by bioindication measures for a number of years. Investigations on living organisms or their remains (e. g. peat) are frequently used to indicate the environmental situation in either qualitative (bioindication) or quantitative (biomonitoring) terms. This provides pieces of information on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Biological monitoring can comprehensively reflect the interaction between various environmental pollution factors and can continuously monitor ecological health (Wang et al, 2010;Markert et al, 2013). The results of the multiple biotic assessment methods showed that Jiaozhou Bay had a good benthic ecological quality status, which was consistent with the results of other studies (Yang et al, 2021;Yin et al, 2021).…”
Section: Evaluation Of Different Biological Indicessupporting
confidence: 82%
“…Biological monitoring can comprehensively reflect the interaction between various environmental pollution factors and can continuously monitor ecological health (Wang et al, 2010;Markert et al, 2013). The results of the multiple biotic assessment methods showed that Jiaozhou Bay had a good benthic ecological quality status, which was consistent with the results of other studies (Yang et al, 2021;Yin et al, 2021).…”
Section: Evaluation Of Different Biological Indicessupporting
confidence: 82%
“…As the BSE was first conceived in 1994, BSE diagrams have been translated into many languages including Chinese (Mandarin), French, German, Latvian, Lithuanian, Persian (Farsi), Polish, Spanish due to the support and discussion from many colleagues around the world. Arabic, Italian, Hindi, Russian, and other translations are being developed [122][123][124][125][126][127][128]. All translations can be found at www.eisninstitute.de.…”
Section: Figurementioning
confidence: 99%